2014
DOI: 10.1186/1743-0003-11-45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task-oriented robot training on arm function, activity, and quality of life in chronic stroke patients: a randomized controlled trial

Abstract: BackgroundOver fifty percent of stroke patients experience chronic arm hand performance problems, compromising independence in daily life activities and quality of life. Task-oriented training may improve arm hand performance after stroke, whereby augmented therapy may lead to a better treatment outcome. Technology-supported training holds opportunities for increasing training intensity. However, the effects of robot-supported task-oriented training with real life objects in stroke patients are not known to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 57 publications
2
88
0
1
Order By: Relevance
“…5 Regarding training physiology, a goal-dependent functional and specific skill training was offered with training loads exceeding the patient's metabolic capacity (overload principle 4 ). As to motor learning principles, 'over-learning strategies' (that is, continued practice after performance), 'exercise variability' to improve patient's motivation and conserve training effect and 'guidance and feedback' 5,9 (provided by the haptic robot device 8,11 ) were used. Patients were offered a task-oriented training, that is, a repetitive training of self-selected, real life activities, to also improve their motivation.…”
Section: Materials and Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Regarding training physiology, a goal-dependent functional and specific skill training was offered with training loads exceeding the patient's metabolic capacity (overload principle 4 ). As to motor learning principles, 'over-learning strategies' (that is, continued practice after performance), 'exercise variability' to improve patient's motivation and conserve training effect and 'guidance and feedback' 5,9 (provided by the haptic robot device 8,11 ) were used. Patients were offered a task-oriented training, that is, a repetitive training of self-selected, real life activities, to also improve their motivation.…”
Section: Materials and Interventionmentioning
confidence: 99%
“…In clinical rehabilitation practice, however, it is well known that high levels of movement repetition and lack of training variation may lead to patients becoming bored, and thus may lead to decreased motivation to train and to lower levels of therapy adherence. To explore the possibilities for extending ToCUEST's training variation, which, in turn, might further improve patients' training motivation, 5,7 the use of training technology was considered, analogous to the work of Timmermans et al, 8,9 who developed and evaluated a technologyassisted task-oriented arm training approach (T-TOAT) for persons with stroke. The use of such a training approach to improve AHSP in persons with C-SCI has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The instrument has been widely used to assess patients with neurodegenerative disease including PD [95][96][97][98], MS [99,100] and stroke [101,102]. It has been largely reported that data collected with the SF-36 questionnaire are of good quality, reliable and that scoring of the subscale scores is appropriate.…”
Section: • • Generic Instruments Short Form Health Survey (Sf-36)mentioning
confidence: 99%
“…Several published studies [11][12][13][14] demonstrate the effectiveness of robotic-assisted therapy in patients with ABI. Almost every study shows that patients receiving assistive robotic training do not show better chances of improving their upper limb movement in most daily living activities.…”
Section: Introductionmentioning
confidence: 99%